Implementación de un sistema de costos basado en actividades para mejorar la gestión financiera de la empresa Full Maquinarias S.A. periodo 2016 - Rodas Cerdán, Mily Gabriela (2018)
Based on the research carried out, it was determined that the problem of the company Full Maquinarias S.A. it is the clear and precise knowledge of the direct and inderect costs of each activity in the productive process of each product offered by the market. Each element of the activities carried out in the productive process was identified, taking as an example 02 basic products of the company Full Maquinarias S.A., determining the expenses of the manufacturing processes are not calculated in detail; why this determines the cost system based on activities to expose the real benefits that the implementation of this system brings. The current calculation of costs was compared, that the company Full Maquinarias SA uses the traditional costing system, which shows that there is a difference of the unit costs calculated in the ABC system and the traditional system of the company, concluding that the company is avoiding activities of which they do not know their exact calculations. In the research it can be concluded that by implementing a cost system in activities, financial management has been improved, which is demonstrated in the distribution of indirect costs, obtaining greater profitability.